Filling some of the gap of ecological information’s of a Brazilian Vulnerable lizard (Tropidurus hygomi) - Santos Caldas, Francis Luiz (2021)
We studied a population of Tropidurus hygomi in an area of geographic disjunction located in Brazil’s Northeast, investigating how individuals use the microhabitats, what is their daily activity in different seasons, how does growth and mass gain occur and what is the sex ratio, besides analyzing the population dynamics and the recruitment period. We collected data patch between January and December 2008 from 6:00 to 18:00 h combining active search techniques, pitfall traps and markings on animals. We observed lizards mainly on sunny days, motionless on the sand near bushes that formed sun and shade mosaic. Sit-and-wait foraging and preference for adequate light supply are conservative behaviors for Tropidurus. The sand allows to quickly achieve optimal thermal conditions. The lizards presented extended activities, with some seasonal differences, but with a more uniformity compared to congeners in other biomes demonstrating influence of local characteristics. We observe sexual dimorphism with larger and heavier males. Distinctions in growth were noticeable between males, females and juveniles (historical influence) but not for mass gain. Sex ratio was displaced in favor of males. This is not common in the genus but could be advantageous for females in choosing better partners. There were fluctuations in population growth, probably related to climate seasonality and mortality in the juvenile phases. Tropidurus hygomi recruitment begins in the rainy season and continues until the beginning of the dry season, unlike other congeners, suggesting the action of ecological effects. We hope that our results will assist in the development of conservation strategies for the populations of T. hygomi that live on the coast (continuous distribution), besides to guiding the execution of new studies.